The Optimalization of Toddler Family Guidance (BKB) in Preventing Child Sexual Abuse - Yuliejantiningsih, Yovitha; Rakhmawati, Dini; Maulia, Desi (Universitas Muhammadiyah Metro, 2019)
The numbers of sexual abuse always increase annually. There is a need for direct involvement from the community. Education about sexual abuse and prevention can be started from toddler family guidance done monthly. This research sees the optimization of toddler family guidance in preventing child sexual abuse. It is a Research and Development using procedures covering the preliminary study, planning, designing an initial product, initial trial run with a small sample, and revising the product. The population involves mothers from the Integrated Health Service of the whole Gunung Pati District divided into 16 administrative villages. The samples of the research are the people of administrative villages with intermediate to lower levels of socio-economy and have 2 – 6-year children. The study uses purposive sampling to collect data using a scaled instrument, questionnaire, and interview. Analyze data used a comparison test.